DESIGN AND DEVELOPMENT OF A 70 N THRUST CLASS TURBOJET ENGINE - Trazzi, P. E. (Revista de Engenharia Térmica, 2004)
Small turbojet engines are being used for propulsion of radio-controlled model airplanes. The design and development of the model 505 small jet engine are reviewed. Small size gas turbines present special design and construction difficulties, some of which are addressed; design choices leading to the final configuration are discussed. Aero-thermodynamic aspects are covered along with experimental data when available. The unit is comprised of a radial compressor, an annular combustion chamber, and an axial turbine plus accessories; details on these components and on production aspects are presented.